GAIT RETRAINING PROGRAM TO REDUCE THE RISK OF REPEAT INJURY IN RUNNERS (LITERATURE STUDY) - Roikhatul Jannah; Bima Akbar Rachsanjani Muawal; Zahra Sativani (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: Nowadays, Sports activities are a necessity for everyone to maintain health and immunity during the pandemic. Running is one of them. But there are things that must be considered, running pattern and postur to reducted risk of injury. About 37% to 79% runner get injured. Gait Retraining Program become training program to reduce risk of running related injury. Purpose: This study is to examine the effectiveness of the program gait retraining in reducing the occurrence of running-related injury. Method: this study uses a literature study method, with a systematic literature study approach. This study used six articles from four different search engines, Pubmed, ResearchGate, PEDro, Portal Garuda. Results: From six literatures, it shows that Gait Retraining Program is effective on Correction running pattern. Conclusion: Gait Retraining Program can change running pattern to become more efficient and lowering ground reaction force impact and distributed to lower limb, that may reduce of risk re-injury. Keywords: Risk Injury, Gait Retraining Program, Runner